Antisemitism and the left On the return of the Jewish question - Spencer, Philip (Manchester University Press, 2018)
"Universalism has always shown two faces to the world: one emancipatory and inclusionary, the other repressive and exclusionary. Jewish experience of universalism has been correspondingly equivocal. Antisemitism and the left provides an original and stimulating study of modern antisemitism, tracing the intellectual and political struggles between these two opposed perspectives. At times, universalism has acted as a stimulus for Jewish emancipation, for civil, political and social inclusion. But it has also been used to justify hatred of Jews, depicting them as hostile to the entire human race, in ways even more sinister than those found in pre-modern and largely Christian traditions of anti-Judaism. A key feature of this repressive and exclusionary universalism and the distinctly modern form of antisemitism it has generated has been the construction of a putative 'Jewish question', which somehow needs to be 'solved'. This book provides conceptual analysis of the struggles waged within the Enlightenment, Marxism, critical Jewish thought and the contemporary left, engaging with such key authors as Mendelssohn, Marx, Adorno and Horkheimer, Arendt and Habermas, to critique the very notion of the 'Jewish question' and rescue universalism from the antisemitic morass into which it has too often fallen. Antisemitism and the left will appeal to students, lecturers and the general reader interested in antisemitism and/or in principles of universalism, spanning the fields of politics, sociology, history, philosophy and Jewish studies. "